Pemahaman Terhadap Hadist Maudhu’ - Dhelta Yendis Tya Putri; M. Habibullah (CV. SINAR HOWUHOWU, 2026)
Everything that is attributed to the Prophet Muhammad SAW. is a source of teachings, insights, and values that are very valuable for Muslims.This study explains the understanding of false hadiths or maudhu' hadiths.This study aims to explain the problems related to false hadiths or maudhu' hadiths. Maudhu' hadiths are lies made and engineered by someone and then attributed to the Prophet Muhammad SAW. False hadiths or maudhu' are as bad as weak hadiths, even some scholars consider them a separate type outside weak hadiths. All scholars agree that narrating false hadiths is haram, except by stating that the hadith is false. However, these false hadiths have spread widely in society, so it is important to provide education to the community so that they know the law.